1992
DOI: 10.1002/ajh.2830410103
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine and prednisone therapy for pure red cell aplasia in patients with chronic lymphocytic leukemia

Abstract: We describe the characteristics of response to treatment with cyclosporine (CYA) plus prednisone in seven episodes of pure red cell aplasia (PRCA) in four patients with B cell chronic lymphocytic leukemia (CLL). Fourteen episodes of PRCA occurred in four patients with CLL. Eleven episodes were treated with conventional therapies which included an alkylating agent and prednisone. Four episodes that failed to respond to conventional therapies and an additional three episodes were treated with CYA and prednisone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 25 publications
(16 reference statements)
2
11
0
Order By: Relevance
“…PRBCA is generally responsive to corticosteroid therapy but patients usually required prolonged high dose therapy or combination therapy to maintain remission26,71. Response should be monitored by measuring the absolute reticulocyte count which usually increases within 2–3 weeks of initiation of therapy while substantial improvements in the hemoglobin level can take up to a month.…”
Section: Managementmentioning
confidence: 99%
“…PRBCA is generally responsive to corticosteroid therapy but patients usually required prolonged high dose therapy or combination therapy to maintain remission26,71. Response should be monitored by measuring the absolute reticulocyte count which usually increases within 2–3 weeks of initiation of therapy while substantial improvements in the hemoglobin level can take up to a month.…”
Section: Managementmentioning
confidence: 99%
“…As previous studies of PRCA had used CsA together with corticosteroids (241, whether CsA alone is effective has not been addressed. Chikkappa et al [5] had also successfully treated PRCA associated with B-cell chronic lymphocytic leukemia with CsA, but concomitant steroids were used as well. Moreover, the starting dose of CsA was 12 mg/kg/day in these studies, and it had been suggested that such a large dose was necessary [6].…”
Section: Pure Red Cell Aplasia Successfully Treated By Cyclosporin a mentioning
confidence: 99%
“…A proportion of these patients, however, eventually require splenectomy or low-dose spleen radiation [84]. Pure red-cell aplasia (PRCA) may occasionally be associated with CLL; good treatment results have been reported with cyclosporine [85].…”
Section: Patients With Cytopenias Due To Immune Mechanismmentioning
confidence: 99%